Analisis Kondisi Pompa Sentrifugal Berdasarkan Getaran Untuk Mencegah Kegagalan Pompa di Kilang Migas Cepu - Fitrian, Ahmad Bagus; Kundori, Kundori (PPPM Polimarin, 2025)
Centrifugal pumps at the PPSDM Migas Refinery play a crucial role in the continuous fluid transfer process. However, these components are prone to various problems, such as misalignment, bearing wear, and imbalance, which can cause serious damage to production downtime. This research aims to analyze the condition of the P100/3 centrifugal pump with a vibration data-based monitoring method. Measurements were taken using a vibration meter with reference to the International Organization for Standardization (ISO) 10816-3 standard on machine classification. Vibration data was collected from three main axes (axial, horizontal, and overhang) for four days to obtain the vibration pattern overhang as well as an indication of potential failures. The measurement results showed that at Non-Drive End (NDE) point 1, the average vibration reached 7.15 mm/s, which is included in zone D (danger), so immediate maintenance is required. Meanwhile, the Drive End (DE) 2, DE 3, and NDE 4 points are in zone B, which is still in the safe category, but still requires regular monitoring. In addition, temperature analysis showed an increase in motor and pump temperatures from August 12 to 16, which although still within reasonable limits, could potentially lead to overheating if not anticipated. Based on these findings, it is concluded that pump P100/3 requires immediate maintenance at point NDE 1, while pump P100/1 is still in a safe condition. Continued maintenance and monitoring recommendations are provided to prevent further potential damage and ensure optimal operational sustainability of the refinery